Microsurgical Reconstruction of Large Oncologic Chest Wall Defects for Locally Advanced Breast Cancer or Osteoradionecrosis: A Retrospective Review of 26 Cases over a 5-Year Period - Arya, Reza; Chow, Whitney T.; Rozen, Warren Matthew; Patel, Nakul G.; Griffiths, Matthew; Shah, Samir; Ramakrishnan, Venkat V. (Journal of Reconstructive Microsurgery, 2016)
Background Locally advanced breast cancer (LABC) and chest wall osteoradionecrosis (ORN) often require extensive and composite tissue resection, including muscles, ribs, pleura, and lung parenchyma. As such, these cases necessitate complex reconstructive procedures for skeletal chest wall reconstruction and soft tissue resurfacing of extensive defects. Traditional local and regional flaps are often inadequate, and many such cases are prospectively labeled “unresectable.”Methods We report a single-center experience with the microsurgical reconstruction of such defects over a 5-year period. Between 2007 and 2011, 1,077 microvascular reconstructive cases following breast cancer resection were performed, of which 26 cases comprised LABC or ORN requiring reconstruction. Surgical indications, defect parameters, choice of reconstruction, and outcomes were assessed.Results Thirty free flap microsurgical reconstructions were undertaken in 26 cases, with a 96.2% flap survival rate. Complications were low, and mean hospital stay was 8.7 days. An algorithmic approach to management is presented.Conclusion Wide resection and microvascular free tissue transfer provide versatile solutions for the reconstruction of extensive chest wall defects. With good reported perioperative outcomes even in advanced cases, surgical resection of LABC may offer a useful approach in difficult and/or palliative cases.
Keywords: soft tissue; skeletal; rib; microsurgery; microvascular; free flap